The Road Performances Analysis on U-Turns in Jalan Raja Alikelana, Batam-Indonesia - Yosua Chester Worang; Amanatullah Savitri (Fakultas Teknik Sipil dan Perencanaan, 2023)
Traffic character is an inseparably interconnected system between volume, speed, and traffic density. In Indonesia, the use of U-turns is often the main impact of road conflicts. Batam is a city with fast economic growth in Indonesia. Therefore, many residents from outside Batam come to work. This affects road performance in Batam where more and more residents are concentrated on Jl. Raja Alikelana. During busy times, such as when people come home from work. Long traffic jams often occur which cause vehicles to be diverted to turn around at the next U-turn. The purpose of this paper is to determine the degree of saturation and the level of road service (LoS) with the IHCM 1997 guidelines. From the survey, the total peak flow data on the first line was 1489.7 pcu/hour and the second line was 1371.9 pcu/hour with degrees of saturation per lane 0.96 and 0.88 with the level of road service for each lane on Jl. Raja Alikelana namely E and D.